Empowering community-based maternal health research: insights from the National Institutes of Health IMPROVE initiative - Ouattara, Balkissa S.; Davis, Maurice; Whitaker, Damiya; Yoon, Sung Sug; Chinn, Juanita; Neilson, Elizabeth; Barr, Elizabeth; Cernich, Alison (Frontiers in Public Health, 2025)
In September 2022, the National Institutes of Health (NIH) launched the Connecting the Community for Maternal Health (CCMH) Challenge as part of the Implementing a Maternal Health and Pregnancy Outcomes Vision for Everyone (IMPROVE) initiative (12). The IMPROVE initiative prioritizes research to reduce preventable maternal mortality, mitigate severe maternal morbidity, and address health disparities. The CCMH challenge sought to reduce maternal health disparities by enhancing research capacity within community-based organizations. Through training, mentorship, research resources, and cash awards, the CCMH challenge empowered local organizations to engage in maternal health research that directly addressed the needs of their communities. By increasing access to NIH resources, the challenge positioned these organizations to contribute sustainably to improved maternal health outcomes. This article provides practical insights into how public health institutions can support community-based research and cultivate partnerships to reduce maternal health disparities. It outlines the competition’s structure, strategies, and outcomes while highlighting key implementation challenges and lessons learned.